New placement for Spaniotoma (Eukiefferiella) claviculata Edwards, 1931 (Diptera: Chironomidae) - Massaferro, Julieta; Donato, Mariano; Brooks, Stephen J. (Zootaxa, 2009)
In a recent examination of Edwards’ Patagonian chironomid types in the Natural History Museum (London, UK) (NHM) we found the species Spaniotoma (Eukiefferiella) claviculata Edwards, 1931, previously considered by Spies & Reiss (1996) as an unplaced valid species, as belonging to the genus Parakiefferiella Thienemann. This species fits all characters in the generic diagnosis of Cranston et al. (1989) by the possession of bare eyes, wings and squama; extended costa; acrostichals absent but with median tuft of microtrichia on scutum; hypopygium with anal point short, broadly based and subtriangular with few basal setae, virga well developed and inferior volsella subrectangular.